Dual modification of tau by pseudophosphorylation and glycation does not enhance amorphous aggregation - Chinnathambi, Subashchandrabose; Sonawane, Shweta Kishor; Chandrashekar, Madhura; Chidambaram, Hariharakrishnan; Thulasiram, Shrivatsa; Kulkarni, Mahesh J. (Cellular Physiology and Biochemistry, 2024)
<h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Background/Aims: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> The neurofibrillary tangles consisting of Tau protein are an important pathology in Alzheimer’s disease. The paired helical filaments of Tau form most of the NFTs. These PHFs of Tau are found to carry numerous post-translational modifications, which stabilize them and aid in aggregation. The mechanistic function of Tau is to bind and stabilize the axonal microtubules. Hyperphosphorylation of Tau causes it to compromise its physiological function and accumulate in the neurons in the form of aggregates. Such residue-specific phosphorylation has been studied by employing Tau pseudophosphorylation mutants. But in addition to phosphorylation, several other modifications also aid in stabilizing the Tau PHF. Glycation is one such non-enzymatic PTM caused by sugars and their reactive intermediates. In this study, we employed the pseudophosphorylated Tau double mutants (262/404D, 262/396D, and 231/262) for studying their modification by methyl glyoxal, a reactive intermediate of glucose metabolism.  <h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Methods: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> We studied various biophysical properties like aggregation propensity, Advanced glycation end-product formation, and global conformation of the Tau with dual modifications. Our study includes the use of <i style="box-sizing: border-box; color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;">in vitro <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;">techniques e.g., ThS fluorescence assay, electron microscopy, CD spectroscopy, SDS-PAGE.  <h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Results: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> The overall result of the study suggest that the MG-induced Tau aggregation is influenced by the residue-specific Tau phosphorylation.  <h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Conclusion: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> In conclusion, the combinatorial effect of discreet PTMs on Tau function could lead to a better understanding of Tauopathy.